Thơ dịch Ức Trai thi tập - Nguyễn Trãi, 1380-1442. (Tp.HCM : Văn nghệ, 1999)
Các tác phẩm thơ của Nguyễn Trãi.
Keywords: Nguyễn Trãi, -- 1380-1442.; Thơ; Văn học Việt; Thi ca Việt -- Nguyễn Trãi, -- 1380-1442.; Nguyễn Trãi, -- 1380-1442.